Genre analysis of introduction section in electrical engineering undergraduate laboratory reports [version 3; peer review: 1 approved, 3 approved with reservations] - Mokhtarrudin Ahmad; Veeramuthu Veerappan; Kavitha Balakrishnan; Mohd Afizal Aris; Wei Hui Suan (F1000Research, 2024)
Background This study examines the genre of Engineering Laboratory Reports (ELR) introduction section written by Electrical Engineering Undergraduates in a higher learning institution. The aims of this study are to identify the rhetorical moves and combinations of move patterns used by electrical engineering (EE) students to write introduction section. Method A genre analysis was conducted to identify writing patterns and convention practices of engineering undergraduate students thus a corpus of N = 35 was selected from electrical engineering students in their final year of study. This study adopted Genre Theory as its theoretical framework, Ngowu 1997 analytical framework and BCU approach for analysis procedure. A pilot test was conducted to determine the model that fits the best to describe moves and steps of ELR. Coding scheme was developed and intercoder reliability showed a significance of 0.91 The study benchmarks a move or step to be present in at least 60% of the reports. Results The finding shows the introduction consists of one main move which is providing background information of the experiment and followed by four subsequent steps which are reference to research purposes, reference to theoretical knowledge in the field, providing an overview of the study and identification of main research apparatus. The move 1 and all four steps identified above are viewed as obligatory, conventional and optional move and steps in introduction section among undergraduates in academic context. The exemplification of finding shows lack of compliance among undergraduates to produce EELR based on university